BASKETBALL: TRANSITION FROM DEFENSE TO ATTACK (Fiep Bulletin - online, 2011)
Believes that basketball is part of the TSG - team sports games, being a team sport with implications that emanate from the need for athletes with specific biotype, requiring the professional who works in this sport to work with different methodologies and contemporary sport pedagogy. Notes that for basketball practice is required from athlete full body employment. Contemporaneously there is no doubt that the offensive in basketball, as the counterattack depends on several factors, and brings us many advantages and can directly influence the progress and the final result of the game, so when the team can be quicklier and put the opponent outnumbered breaking his offensive balance (quick turn from attack to defense). It is said that counterattack surprises the opponent when, still, they are organizing their defense, creating with it, the numerical superiority of offensive action. To realize the counterattack properly it takes also into consideration the type of defense that they do, but, whether individually or in the defense area, there are important points and principles to be followed. The sequence showed that it related to the counterattack corresponds to action that takes place among players and trainer / coach, and that in my point of view represents a determinant factor in basketball quality development.It is observed that the coach has the responsibility of the individual technique of his players, and also disciplinary actions, opinions, comments and considerations related to the interests of the team's success. so, basketball is a highly dynamic game, and so there must be dynamism in their trainings, especially regarding the speed to go from defense to attack, what is called contemporary rapid transition from defense to attack.
Keywords: Basketball; counterattack; transition